'History Obliges' The Real Motivations Behind German Aid Flows in the Case of Namibia - Schuring, Esther (Tufts Archival Research Center, 2005)
Submitted in partial fulfillment of the degree of Master of Arts in Law and Diplomacy at the Fletcher School of Law and Diplomacy. Abstract: This study explains the exceptional donor position that Germany assumes in Namibia. Contrary to the predominant discourse on aid allocation literature, this study finds that classic motives such as need, economic potential, strategic interest in military terms, democracy and region do not factor in as strongly in Namibia's case. Germany's aid flows are largely a result of two variables, (1) moral obligation, a largely understudied variable and (2) cultural similarity, a variable not often applied in the German context due to the removed colonial presence. Moral obligation is mainly a product of German-Namibian colonial history -the 'genocide' that the emperor's troops executed in 1904-07, reinforced by the largely contested German aid flows to Namibia during South African occupation. The recognition of colonial wrongdoings by German politicians, coupled with external pressure have turned moral obligation into the most decisive variable in the German-Namibian aid relationship. Whereas internal pressure has been almost non-existent, external pressure has been exerted continuously and successfully by the Namibian government and by the Herero. Worried about its reputation and costly reparations, the German government appears to have used its generous aid flows in an attempt to silence these pressure sources. The second most influential variable, the cultural similarity to the 20,000 Namibia Germans, has political as well as sentimental roots: German politicians have cared and continue to do so for their constituency in Namibia and in no other country, the German language and traditions play such a significant role as in Namibia. Next to these two prevalent variables, a third variable has increasingly gained more momentum. Although not one of the predominant determinants of German aid flows, the socio-political strategic interest of the German government to placate potential tensions arising from the land reform issue has guaranteed that aid continues to flow. This variable is a combination of moral obligation (land reform as colonial legacy) and cultural similarity (concern about the well-being of the Namibia Germans).